Industrial strengths and clusters in the East Midlands - Mole, Richard (2007)
The intension of this study was to identify the industrial highlights and strengths of the East Midlands region, both at the regional and local administrative area level. In addition, representative companies of each highlighted industry were identified. The purpose of this information was to help inform and assist a regional Venture Capital Fund (East Midlands Early Growth Fund) in their deal generation and assessment activities. This cross-sectional survey used three sources of data: 1. Employment data statistics were used to identify industrial highlights. 2. A company report database was used to generate a list of companies present within each industrial highlight. 3. A survey of local economic development professionals cross referenced secondary sources as well as provided additional information. Industrial highlights or strengths were identified for the East Midlands Region and all 40 constituent areas along with a number of exemplar companies. Analysis of the geographical distribution of these strengths identified some agglomerations of industries that may be indicative of the presence of clusters: 1. Agricultural cluster centred in Lincolnshire with specific strengths in poultry and Fruit & Vegetable production and processing. 2. Food processing, located across the region 3. Plastics manufacture around Nottingham and Corby/ Rutland. 4. Textiles, with specific strengths in footwear manufacture in Northamptonshire, and kitted and crocheted fabric around Leicester and Ashfield/ Amber Valley. 5. Furniture manufacture, particularly production of seats and chairs to the west of the City of Nottingham (Erewash). 6. Construction, with highlights in concrete manufacture. 7. Light engineering, specifically with highlights in engine manufacture, including both electrical motors and non-electrical engines, as well as the transport equipment sector, with specific loci around Derby in the rail (or tram) and aerospace industries.